Influence of polyploidy on insect herbivores of native and invasive genotypes of Solidago gigantea (Asteraceae) - Hull-Sanders, Helen M (Landes Bioscience, 2009)
Herbivores are sensitive to the genetic structure of plant populations, as genetics underlies plant phenotype and host quality. Polyploidy is a widespread feature of angiosperm genomes, yet few studies have examined how polyploidy influences herbivores. Introduction to new ranges, with consequent changes in selective regimes, can lead to evolution of changes in plant defensive characteristics and also affect herbivores. Here, we examine how insect herbivores respond to polyploidy in Solidago gigantea, using plants derived from both the native range (USA) and introduced range (Europe). S. gigantea has three cytotypes in the US, with two of these present in Europe. We performed bioassays with generalist (Spodoptera exigua) and specialist (Trirhabda virgata) leaf-feeding insects. Insects were reared on detached leaves (Spodoptera) or potted host plants (Trirhabda) and mortality and mass were measured. Trirhabda larvae showed little variation in survival or pupal mass attributable to either cytotype or plant origin. Spodoptera larvae were more sensitive to both cytotype and plant origin: they grew best on European tetraploids and poorly on US diploids (high mortality) and US tetraploids (low larval mass). These results show that both cytotype and plant origin influence insect herbivores, but that generalist and specialist insects may respond differently.